2009
DOI: 10.1177/0269215509339000
|View full text |Cite
|
Sign up to set email alerts
|

The consequences of early discharge after hip arthroplasty for patient outcomes and health care costs: comparison of three centres with differing durations of stay

Abstract: Short postoperative stay after hip arthroplasty can be achieved without intensive patient preparation or post-discharge care and without compromising short-term patient outcome or increasing health care costs. Longer term follow-up is needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
41
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(55 citation statements)
references
References 27 publications
1
41
0
Order By: Relevance
“…It has been suggested that physiotherapy provided after discharge is not necessary to achieve excellent short-term recovery. 616 The clinical reasoning around the decision not to provide additional physiotherapy following THR was not explored but may reflect the uncertain evidence supporting long-term benefits of physiotherapy after hip replacement, 253 despite many patients continuing to have persistent muscle weakness and functional deficits compared with their age-matched peers 592 up to 2 years after surgery.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that physiotherapy provided after discharge is not necessary to achieve excellent short-term recovery. 616 The clinical reasoning around the decision not to provide additional physiotherapy following THR was not explored but may reflect the uncertain evidence supporting long-term benefits of physiotherapy after hip replacement, 253 despite many patients continuing to have persistent muscle weakness and functional deficits compared with their age-matched peers 592 up to 2 years after surgery.…”
Section: Discussionmentioning
confidence: 99%
“…The advantages of fast-track are well documented from both socio-economic perspectives (Andersen et al, 2009;Hunt et al, 2009;Larsen et al, 2009) and from the perspective of improved outcome for patients (Dowsey et al, 1999;Kehlet, 2013;Kehlet and Wilmore, 2008) including reduced incidence of complications (Husted et al, 2010b(Husted et al, , 2010cSavaridas et al, 2013). Furthermore, the readmission rate is reported not to be higher in a fast-track setting compared with a conventional setting (Husted et al, 2010b).…”
Section: Introductionmentioning
confidence: 99%
“…23 A previous report showed that median stay of three days can be achieved with no more rehabilitation input than routine in-hospital physiotherapy, with no impairment to clinical outcomes and without cost-shifting. 4 The present report shows that this median stay can be achieved with no detriment to patient experience and, by contrast, with indications of improved experience. The evidence therefore shows no benefit of prolonging patients' hospital stay beyond a median of three days after this procedure.…”
Section: Discussionmentioning
confidence: 44%
“…In primary hip arthroplasty patients six weeks postoperatively, patient-reported outcomes, including quality of life, mental state and physical function, were all at least as good in a unit with accelerated discharge as in two units with longer stay. 4 For shorter stay to be adopted more widely it needs to be shown to be acceptable to patients, whose evaluations of care have become important in health policy. The aim of this study was to compare patients' evaluation of hip arthroplasty between a unit with accelerated discharge and two comparison units representing different models of care in the UK.…”
Section: Introductionmentioning
confidence: 99%